Effect of lengthening rate on angiogenesis during distraction osteogenesis. - Li, G; Simpson, A; Kenwright, J; Triffitt, J (J Bone Jt Surgery Inc., 1999)
This study investigated the angiogenic response to four varying rates (0.3, 0.7, 1.3, and 2.7 mm/day) of distraction in a rabbit model of leg-lengthening. Immunostaining was performed with use of specific antibodies to type-IV collagen and endothelial cell antigen to examine semiquantitatively the presence of blood vessels in the developing tissues. With use of the Chalkley counting method, the greatest number of positive-staining blood vessel cells was found in the central fibrous zone of the groups that underwent lengthening at 0.7 and 1.3 mm/day compared with any other zone in any group (p < 0.05, t test). There were no statistical differences in the positive labeling indices in the mineralization front and the new bone zone adjacent to the mineralization front in any of the groups. However, the decrease in the number of positive-staining blood vessel cells in the new bone zone distant to the mineralization front compared with any other zone in any group was statistically significant. The results suggest that during distraction osteogenesis, the precursor cells of new capillaries were present in abundance within the fibrous interzone. These cells connected into the capillary network at the junction of the mineralization front and the fibrous zone. The angiogenic response was weaker in the more mature regions within the new bone zones. A slow rate of distraction (0.3 mm/day) did not maximally stimulate angiogenesis in the central fibrous zone, whereas high rates (2.7 mm/day) appeared to impair this response. In this model of distraction osteogenesis, the vascularization process in the central fibrous zone was maximally stimulated at distraction rates of 0.7 and 1.3 mm/day.